THE STUDY OF ETHNOMATHEMATIC OBJECTS IN THE DIENG TEMPLE WONOSOBO, CENTRAL JAVA - Rina Mahmudati; Siti Lailiyah (IAIN Ambon, 2020)
The development of science and technology which is based on mathematics must be balanced with human resources who are sensitive to changing times without leaving the national identity achieved through learning in schools. Exploration of Dieng Temple objects as historical artifacts in Wonosobo can produce knowledge about the structure and architecture of Dieng Temple which can be used as a source of contextual learning. The purpose of this study was to determine the ethnomathematics object contained in the Dieng temple. The research method used is qualitative research. Data collection methods are observation and interviews with 1 archaeologist and 2 local cultural observers. The results of this study indicate that there are ethnomathematics objects that can be applied in mathematics learning in historical buildings, one of which is the Dieng Temple. A well-observed indicator is an activity of generalizing the number sequence pattern and the object configuration sequence pattern